The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1111/aor.12151
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Hemodynamics During Extended Continuous Flow Left Ventricular Assist Device Support: The Response of Systemic Cardiovascular Parameters and Pump Performance

Abstract: Patients on continuous flow left ventricular assist devices (cf-LVADs) are able to return to an active lifestyle and perform all sorts of physical activities. This study aims to evaluate exercise hemodynamics in patients with a HeartMate II cf-LVAD (HM II). Thirty (30) patients underwent a bicycle exercise test. Along with exercise capacity, systemic cardiovascular responses and pump performance were evaluated at 6 and 12 months after HM II implantation. From rest to maximum exercise, heart rate increased from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 38 publications
3
43
0
Order By: Relevance
“… EmaxL : among all the investigated parameters, EmaxL is one of the most important in assuring a higher TCO at exercise. These results are in line with previous clinical studies evidencing the crucial role of the residual LV function in eliciting a higher TCO and exercise capacity . Noor et al observed that patients with a residual LV contractility are able to better accommodate an increase in TCO, resulting in higher exercise capacities.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… EmaxL : among all the investigated parameters, EmaxL is one of the most important in assuring a higher TCO at exercise. These results are in line with previous clinical studies evidencing the crucial role of the residual LV function in eliciting a higher TCO and exercise capacity . Noor et al observed that patients with a residual LV contractility are able to better accommodate an increase in TCO, resulting in higher exercise capacities.…”
Section: Discussionsupporting
confidence: 91%
“…Current LVADs work at a constant pump speed and do not embed physiological controllers to adapt the support to body needs at exercise. Therefore, patients mainly rely on their remaining cardiac function to increase TCO by the output through the aortic valve (Q AV ) and achieve higher peak VO 2 levels . Dependencies between low LVAD speed (below baseline value) and reduced exercise capacities were found in the previous clinical studies .…”
Section: Introductionmentioning
confidence: 93%
“…The key determinates for a decreased pump head are increasing venous return and LV contractility or reducing afterload, for example, due to vasodilation. These effects occur as a cardiovascular response during exercise depending on exercise intensity and duration .…”
Section: Discussionmentioning
confidence: 99%
“…(18,2224) By 6 months, peak VO 2 ranged from 12.7 to 18.7 mL/kg/min. (21,2426) Percentage of predicted norms reflected these increases with percentages increasing from 48–61% at 1 month to 42–66% at 12 months. (2428) These large improvements illustrated that patients function better after LVAD, however function remained significantly below age-adjusted norms.…”
Section: Describing Functional Progressmentioning
confidence: 94%